Polysaccharides from Dendrobium huoshanense stems alleviates lung inflammation in cigarette smoke-induced mice. (1st June 2018) - Ge, Ji-Chun; Zha, Xue-Qiang; Nie, Chun-Yan; Yu, Nian-Jun; Li, Qiang-Ming; Peng, Dai-Yin; Duan, Jun; Pan, Li-Hua; Luo, Jian-Ping
Highlights: The cultivated D. huoshanense stem polysaccharide (cDHP) mainly consisting of 1, 4-Man, 1, 4-Glc, 1, 4, 6-Man and T-Glc. CDHP can alleviate lung inflammation in cigarette smoke-induced mice. The anti-inflammation function of cDHP is mediated via regulating NF-κB and MAPK signaling. Abstract: The present work investigated the inhibitory activity of the polysaccharide from cultivated Dendrobium huoshanense (cDHP) on lung inflammation in cigarette smoke (CS)-induced mouse model. cDHP was mainly composed of mannose and glucose in a molar ratio of 1.89: 1.00, and had a backbone with linkages of 1, 4-Man p, 1, 4-Glc p, 1, 4, 6-Man p and 1-Glc p . Hematoxylin and Eosin (HE) staining and immunohistochemistry analysis showed that cDHP can increase alveolar number, thicken alveolar wall, inhibit pulmonary bulla formation and decrease inflammatory cell infiltration as compared to the model group. ELISA determination revealed that cDHP can inhibit CS-induced enhancement in TNF-α and IL-1β secretion in serum and lung. These results suggested that cDHP can resist CS-induced lung inflammation. Further, the phosphorylation analysis of p65, IκB, p38 and JNK as well as the DNA binding activity analysis of NF-κB and AP-1 implied that the anti-inflammation function of cDHP is mediated via regulating NF-κB and MAPK signaling.